PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK PADA MATERI PENCEMARAN LINGKUNGAN (Studi Eksperimen di Kelas X SMA Negeri 1 Cihaurbeuti Tahun Ajaran 2015/2016) - Endang Surahman (Bioedusiana: Jurnal Pendidikan Biologi, 2016)
Abstract: The aimed of this research was to know the influence of problem basedlearning model to creative thinking skills on environmental pollution material in Xgrade of SMA Negeri 1 Cihaurbeuti at 2015/2016 academic year.This research was conducted from November 2015 until March 2016 in X grade ofSMA Negeri 1 Cihaurbeuti. The method used in this research was true experiment.The population of this research was all class of X grade at SMA Negeri 1Cihaurbeuti as much as 4 classes which consist of 144 student. The sample used in the research which taken by cluster random sampling technique as much as two class, X MIPA 1 as the experimental class and X MIPA 2 as the control class. To measure the creative thingking skills, used an instrument that is a test of the creative thingking skills which consists of 11 questions in the form of essay. Analysis using t test with significance level α = 0,05. The result of the research shows there was influence of problem based learning model to creative thinking skills on environmental pollution material (an experimental study in X grade of SMA Negeri 1 Cihaurbeuti academic year 2015/2016).Keywords: problem based learning model, creative thinking skills and environmental pollution